2009
DOI: 10.1590/s1413-81232009000500021
|View full text |Cite
|
Sign up to set email alerts
|

Rompendo com a criminalidade: saída de jovens do tráfico de drogas em favelas na cidade do Rio de Janeiro

Abstract: Rompendo com a criminalidade: saída de jovens do tráfico de drogas em favelas na cidade do Rio de JaneiroStopping with the criminality: a way out of youths involved in traffic of drugs in slums in the city of Rio de Janeiro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 0 publications
0
4
0
10
Order By: Relevance
“…In addition, it was found that in neighborhoods that differed in terms of five or more persons involved in drug trafficking there was a 40% increase in the coefficient of intentional homicide. A study by Meirelles et al 24 , which was carried out in Rio de Janeiro in 2004, also showed an association of around 90% between drug trafficking and homicides. In his study of drug policies in Brazil, Andrade 3 also linked drug trafficking with cases of homicide.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, it was found that in neighborhoods that differed in terms of five or more persons involved in drug trafficking there was a 40% increase in the coefficient of intentional homicide. A study by Meirelles et al 24 , which was carried out in Rio de Janeiro in 2004, also showed an association of around 90% between drug trafficking and homicides. In his study of drug policies in Brazil, Andrade 3 also linked drug trafficking with cases of homicide.…”
Section: Discussionmentioning
confidence: 89%
“…The trajectories of youngsters who 'turn their back' are often marked by circumstances of great vulnerability and this departure is often a dangerous, long and drawn out affair, as Meirelles and Minayo Gomez (2009) have shown. Social networks of support and protection are of extreme importance in successfully navigating this process.…”
Section: Perceptions On the Implementation Of The Upps And Consequentmentioning
confidence: 99%
“…Na déca-da de 1990, a faixa de idade era de 15 a 16 anos, e a partir do ano 2000 essa média passou a se situar entre 12 e 13 anos. Os principais fatores que motivam os jovens a ingressar no tráfico de drogas são a perspectiva de ganhos econômicos e desejo de bens de consumo 12 .…”
Section: "Eu Acho Que Não Muda Mais Eles Já Se Acostumaram Nada Maiunclassified